Regulation of the skeletal muscle blood flow in humans - Mortensen, S. P.; Saltin, B. (Experimental Physiology, 2014)
What is the topic of this review?: This review highlights recent advances in our knowledge about the control of skeletal muscle blood flow during exercise in humans.